Evidence cornered: Preoperative intravenous iron to treat anaemia before major abdominal surgery (PREVENTT trial). Issue 5 (28th June 2021) - Aaron, Louise; Day, James; Shah, Akshay
Abstract: Clinical question: Does intravenous iron given to anaemic patients (haemoglobin [Hb] <130 g/L for men and 120 g/L for women) before major elective open abdominal surgery reduce the need for blood transfusions or death within 30 days of surgery? Evidence from trial: There were no significant differences in the rates of blood transfusion or death at 30 days after the index operation between anaemic patients who received intravenous iron preoperatively and those who did not.